The Partnership between Indonesia and United Kingdom to Achieve the NetZero Emission Goal on Behalf of Sustainable Development Action - muhammad dipta arkantyo; ningsih susilawati; ida bagus putu aditya; indra krishnamurti (LIAISON JOURNAL OF BEST, 2023)
This study has investigated Indonesia and UK bilateral cooperation, particularly in the sustainable development sector initiated by domestic agenda and international pressure through the United Nations, which created a sub-organization, United Nations Framework Convention Climate Change (UNFCCC) which focuses on climate change and sustainable development. With that, UNFCCC set a standard for countries by creating a Paris Agreement and set long-term goals for countries to achieve Net-Zero Emission Goal as a commitment to sustainable development. Therefore, it opened the first collaboration of Indonesia-UK, namely the United Kingdom Climate Change Unit Indonesia (UKCCU Indonesia) and continuing with the United Kingdom Partneringfor Accelerated Climate Transitions (UK-PACT) as well as the MENTARI program (Towards Indonesia’s Low Carbon Energy Transition which this program progressively helps two countries in achieving Net-Zero Emission Goal by implementing low carbon development, green economy, green growth, and green jobs, as well as this research, identify opportunities and challenges of thiscollaboration such as green investment, high reciprocity, COVID-19 pandemic situation, lack of funding, competing for interest, and greenwash issue that analyze by using theories such as international cooperation theory and green economy theory as well as qualitative method through public references and interview data collection which can enrich the research discussion. Keywords: Indonesia; United Kingdom; Climate change; International cooperation; Green economy